If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 60 = 6x Reorder the terms: 60 + x = 6x Solving 60 + x = 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 60 + x + -6x = 6x + -6x Combine like terms: x + -6x = -5x 60 + -5x = 6x + -6x Combine like terms: 6x + -6x = 0 60 + -5x = 0 Add '-60' to each side of the equation. 60 + -60 + -5x = 0 + -60 Combine like terms: 60 + -60 = 0 0 + -5x = 0 + -60 -5x = 0 + -60 Combine like terms: 0 + -60 = -60 -5x = -60 Divide each side by '-5'. x = 12 Simplifying x = 12
| 7y^3-27y^2-4t=0 | | 2-2x=-8(5+2x) | | 3x-6+2=2x-20 | | 2w^2=18w | | 3-7(7k-7)=10-7k | | 4(y-5)=2(y-10) | | W^2-2w-35=0 | | x=6x+60 | | 0=-7c-13 | | 5(3x-13)=10 | | 3b^2=21b | | 5x^2+4x-20=0 | | 3(y-5)+2(3+y)=21 | | 12-x=-(x+12) | | 7x+17=101 | | 7x-21=42 | | .333(18x-12)=2(3x-2) | | 117-(-60)= | | 25x-5=3x+6 | | .5(x+4)=2+.5x | | x+8=x+12 | | 2e^4x-11=0 | | 2(2-3x)=-6(x+2) | | 2(e^4x-3)=8 | | 11+5=5+47 | | 6x-19=4y | | t=cm | | 7(x-2)=4(2x+1) | | 8y-6=5y | | a^2+2ab+b^2=y | | 6-x=x+6 | | 3x-5=3x+7 |